Prothymosin‐alpha preconditioning activates TLR4–TRIF signaling to induce protection of ischemic retina. (16th October 2015) - Halder, Sebok Kumar; Matsunaga, Hayato; Ishii, Ken J.; Ueda, Hiroshi
Abstract: Prothymosin‐alpha protects the brain and retina from ischemic damage. Although prothymosin‐alpha contributes to toll‐like receptor (TLR4)‐mediated immnunopotentiation against viral infection, the beneficial effects of prothymosin‐alpha‐TLR4 signaling in protecting against ischemia remain to be elucidated. In this study, intravitreal administration of prothymosin‐alpha 48 h before induction of retinal ischemia prevented retinal cellular damage as evaluated by histology, and retinal functional deficits as evaluated by electroretinography. Prothymosin‐alpha preconditioning completely prevented the ischemia‐induced loss of ganglion cells with partial survival of bipolar and photoreceptor cells, but not amacrine cells, in immunohistochemistry experiments. Prothymosin‐alpha treatment in the absence of ischemia caused mild activation, proliferation, and migration of retinal microglia, whereas the ischemia‐induced microglial activation was inhibited by prothymosin‐alpha preconditioning. All these preventive effects of prothymosin‐alpha preconditioning were abolished in TLR4 knock‐out mice and by pre‐treatments with anti‐TLR4 antibodies or minocycline, a microglial inhibitor. Prothymosin‐alpha preconditioning inhibited the retinal ischemia‐induced up‐regulation of TLR4‐related injury genes, and increased expression of TLR4‐related protective genes. Furthermore, the prothymosin‐alpha preconditioning‐induced prevention of retinal ischemic damage was abolished in TIR‐domain‐containing adapter‐inducing interferon‐β knock‐out mice, but not in myeloid differentiation primary response gene 88 knock‐out mice. Taken together, the results of this study suggest that prothymosin‐alpha preconditioning selectively drives TLR4–TIR‐domain‐containing adapter‐inducing interferon‐β signaling and microglia in the prevention of retinal ischemic damage. We propose the following mechanism for prothymosin‐alpha (ProTα) preconditioning‐induced retinal prevention against ischemia: ProTα preconditioning‐induced prevention of retinal ischemic damage is mediated by selective activation of the TIR‐domain‐containing adapter‐inducing interferon‐β (TRIF)– interferon regulatory factor 3 (IRF3) pathway downstream of toll‐like receptor 4 (TLR4) in microglia, resulting in up‐regulation of TRIF‐IRF3‐dependent protective genes and down‐regulation of myeloid differentiation primary response gene 88 (MyD88)‐Nuclear factor (NF)κB‐dependent injury genes. Detailed investigations would be helpful to test the efficacy of ProTα as a therapeutic agent for the prevention of ischemic disorders. Abstract : We propose the following mechanism for prothymosin‐alpha (ProTα) preconditioning‐induced retinal prevention against ischemia: ProTα preconditioning‐induced prevention of retinal ischemic damage is mediated by selective activation of the TIR‐domain‐containing adapter‐inducing interferon‐β (TRIF)– interferon regulatory factor 3 (IRF3) pathway downstream of toll‐like receptor 4 (TLR4) in microglia, resulting in up‐regulation of TRIF‐IRF3‐dependent protective genes and down‐regulation of myeloid differentiation primary response gene 88 (MyD88)‐Nuclear factor (NF)κB‐dependent injury genes. Detailed investigations would be helpful to test the efficacy of ProTα as a therapeutic agent for the prevention of ischemic disorders.